Study on Mechanical and Tribological Characterization of Titanium Diboride (TiB2) Reinforced Al7075 Composites by Taguchi Technique - Suhas B G; Chidanand Kishor MANGRULKAR; kiran K.U.; Umesh G L (Journal of Materials and Engineering Structures)
Three distinct titanium diboride (TiB2) weight percentages 3%, 6%, and 9% were incorporated into Al7075-TiB2 composites by stir casting. Al7075-TiB2 composites' wear and mechanical characteristics were evaluated. The microstructural investigation titanium diboride verified the stable interfacial bond between the matrix and reinforcing material as well as the uniform distribution of TiB2 particles. Superior mechanical properties were noted when comparing the 9% TiB2 composites to the 3 and 6% TiB2 composites. The tensile strength was increased by 11.94% for 9% TiB2 reinforced Al composites. Dry sliding wear was measured with pin-on-disc device. Measurements of the samples' wear loss as well as coefficient of friction (COF) showed that the cumulative wear loss for each composite varied linearly with load. As seen by the optical microscope, all specimens within the prescribed tension and sliding distance appear to have oxidative wear on the worn-out surfaces of the wear mechanism. Wear rate is most affected by weight percentage TiB2 (48.43%), followed by load (19.08%), according to the ANOVA. The wt. % of TiB2, at 37.68%, has the biggest effect on the COF, followed by sliding distance (20.54%). Taguchi technique validates the beneficial impact of weight percentage TiB2 on wear loss and COF. The composite reinforced with 9% TiB2 has the finest tribological and mechanical properties.